2013
DOI: 10.1002/joc.3834
|View full text |Cite|
|
Sign up to set email alerts
|

Climatology, annual cycle and interannual variability of precipitation and temperature in CORDEX simulations over West Africa

Abstract: We examine the ability of an ensemble of 10 Regional Climate Models (RCMs), driven by ERA-Interim reanalysis, in skillfully reproducing key features of present-day precipitation and temperature (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) over West Africa. We explore a wide range of time scales spanning seasonal climatologies, annual cycles and interannual variability, and a number of spatial scales covering the Sahel, the Gulf of Guinea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
131
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 93 publications
23
131
0
Order By: Relevance
“…Diallo et al 2012Diallo et al , 2013aHernán-dez-Díaz et al 2013;Nikulin et al 2012;Gbobaniyi et al 2013;Sylla et al 2013b). …”
Section: Precipitation Climatologymentioning
confidence: 99%
“…Diallo et al 2012Diallo et al , 2013aHernán-dez-Díaz et al 2013;Nikulin et al 2012;Gbobaniyi et al 2013;Sylla et al 2013b). …”
Section: Precipitation Climatologymentioning
confidence: 99%
“…Even though this study showed the high potential of RegCM3 to handle very subtle interactions between the AEWs and the AEJ, it was quite limited in terms of quantitative evidence, such as the extent to which this synoptic-scale activity determines the monsoon precipitation. The recent studies by Gbobaniyi et al (2013), Diallo et al (2014) and Mounkaila et al (2015) broadly show a good representation of the WAM onset by RCMs participating in COR-DEX. Mariotti et al (2014) have shown better performance of RCMs in comparison with GCMs in reproducing the AEW activity, but their analysis is qualitative.…”
Section: Introductionmentioning
confidence: 75%
“…Vellinga et al 2013;Fitzpatrick et al 2015), two main features can be used for detecting the onset: (1) the large-scale onset that focuses on the shift (or jump) of the sustained rainy band from its Guinean position (~5°N) to a Sudanese position (~10°N), (2) the local onsets are related to more agricultural purposes and represent the effective start of sustained rainfall at a specific location. The large-scale precipitation onset has been quite widely analyzed, in particular in CORDEX simulations (among others, Gbobaniyi et al 2013;Nikulin et al 2012;Diaconescu et al 2015) and most RCMs tend to improve the onset occurrence in comparison with ERAI and GCMs. The local onset is more complicated to reproduce since precipitation structures are more affected by smaller scale processes in this case (Marteau et al 2011).…”
Section: Methodology and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of temperature and precipitation biases in all the seasons was not horizontally homogeneous, but appeared to be more intense over areas with complex terrains (e.g., Guinean Highlands, Cameroon Mountains, and Jos plateau in Nigeria). Previous regional climate model simulations over West Africa reported similar biases [18,30,[60][61][62][63][64]. The model biases were associated with different factors, such as the absence of sufficient observing stations in the mountainous region, the influence of land/sea boundary conditions, physics configuration of the model, inherited biases from the driving global circulation models (GCMs), or the choice of cumulus convective parameterization [39,[65][66][67].…”
Section: Regcm4 Model Validationmentioning
confidence: 83%